The theology of Pope Benedict XVI: the christocentric shift - Gáal, Emery de (Palgrave Macmillan, 2010)
"Many refer to Pope Benedict XVI as "the Mozart of Theology." Who are the personalities and thinkers who have informed his theology? What events, and which religious devotions, have shaped his personality? What are the central themes of his complex scholarship encompassing more than 1500 titles? This study attempts to shed light on the unifying melody of the policies and positions of a pontificate charged with spiritual and theological depth. Especially in the 1970s an anthropocentric shift had occurred. Emery de Gal̀ argues that, amid a general lack of original, secular ideas stirring public opinion, Benedict XVI inaugurates an epochal Christocentric shift; by rekindling the Patristic genius, he provides Christianity with both intellectual legitimacy and the scholarship needed to propel it into the twenty-first century"--